The Hitchhiker Position in Endoscopic Pituitary Surgery. Issue 5 (29th November 2022) - Kilgallon, John L.; Thorne, Alison; Laws, Edward R.
Abstract : BACKGROUND: Technically and ergonomically correct positioning is essential in endoscopic transsphenoidal pituitary surgery. OBJECTIVE: To propose a safe, ergonomic approach to conduct endoscopic endonasal pituitary and skull base surgery in large patients without sacrificing important aspects of current standard practice. METHODS: The patient's right arm is outstretched and secured in a supine position, with the primary surgeon standing in the axillary area. Considerations include maintaining comfort, immobility, anesthesia access, endotracheal tube fixation, intravenous lines, thorax elevated 25° to 30° for optimization of respiration, free and exposed abdomen for fat graft, legs positioned with no sciatic stretch or venous strain, and the patient's head in parallel with the surrounding area to sustain a strict midline. RESULTS: Ten patients who underwent transsphenoidal pituitary tumor resections conducted using the hitchhiker position from October 2019 to June 2021 comprised our study cohort. The patients' mean height was 168.70 ± 9.29 cm, their mean weight was 114.35 ± 19.32 kg, and their mean body mass index was 40.19 ± 6.39 kg/m 2 . Twenty percent (n = 2) patients had a body mass index classified as "obesity class 1, " 50% (n = 5) as "obesity class 2, " and 30% (n = 3) as "extreme obesity class 3." The primary surgeon consistently reported decreased bodily strain and improved ergonomic access to the surgical site using the hitchhiker position. CONCLUSION: The hitchhiker position offers the opportunity to improve both patient and physician well-being in the context of endoscopic pituitary surgery.